The Java programming language - Arnold, Ken (Addison-Wesley, 1996)
Coauthored by the creator of the Java technology, The Java Programming Language is the definitive resource for all serious Java programmers. This book will give you a solid foundation in Java programming language strategies and techniques. It features a concise introduction to the language and detailed descriptions of Java's commands, constructs, and libraries, and includes numerous real-world examples that show you how to exploit the language's power, portability, and flexibility. You will find in-depth and progressively advanced coverage of classes and objects, interfaces, exception-handling, threads and multitasking, and packages. In addition, the book describes the Java core library packages, including I/O, standard utilities, language types, and system classes.